Application model of k-means clustering: insights into promotion strategy of vocational high school - Abadi, Satria; Shukri Mat The, Kamarul; Mohd. Nasir, Badlihisham; Huda, Miftachul; L. Ivanova, Natalie; Indra Sari, Thia; Maseleno, Andino; Satria, Fiqih; Muslihudin, Muhamad (International Journal of Engineering and Technology, 2018)
Admission process is required in promoting the strategy to achieve the target. Through determining the strategic promotion, minimizing the cost in the marketing process could be reached with determining the appropriate promotion strategy. Data mining techniques in this initiative were applied to achieve in determining the promotional strategy. Using Clustering K-Means algorithm, it is one method of non-hierarchical clustering data in classifying student data into multiple clusters based on similarity of the data, so that student data that have the same characteristics are grouped in one cluster and that have different characteristics grouped in another cluster. Implementation using Weka Software is used to help find accurate values where the attributes include home address, school of origin, transportation, and reasons for choosing a school. The cluster of students was classified into five clusters in the following: the first cluster 22 students, the second cluster 10 students, the third cluster 10 students, the fourth cluster a total of 33 students, and the fifth cluster 25 students. The pattern of this result is supposed to contribute to enhance the significant data mining to support the strategic promotion in gaining new prospective students.Â Â